2012
DOI: 10.3126/kumj.v9i4.6339
|View full text |Cite
|
Sign up to set email alerts
|

C–reactive Protein and Early Mortality in Acute Ischemic Stroke

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 25 publications
2
21
1
1
Order By: Relevance
“…Data demonstrated that elevated CRP in plasma could predict not only future vascular events in healthy individuals, but also an increased risk of fatal or nonfatal cerebrovascular events in ischemic stroke patients 12. Elevated CRP levels at admission are significantly associated with early neurologic deterioration 13, poorer functional outcome, both short- and long-term mortality after stroke 14-15 and predict a larger infarct size 16-17. Our study provides further evidence that elevated CRP could be served as a biomarker for the diagnosis of non-cardioembolic stroke subtype, especially within 1 day of stroke onset.…”
Section: Discussionmentioning
confidence: 99%
“…Data demonstrated that elevated CRP in plasma could predict not only future vascular events in healthy individuals, but also an increased risk of fatal or nonfatal cerebrovascular events in ischemic stroke patients 12. Elevated CRP levels at admission are significantly associated with early neurologic deterioration 13, poorer functional outcome, both short- and long-term mortality after stroke 14-15 and predict a larger infarct size 16-17. Our study provides further evidence that elevated CRP could be served as a biomarker for the diagnosis of non-cardioembolic stroke subtype, especially within 1 day of stroke onset.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies evaluated for the co-morbidities showed predominance of hypertension and diabetes mellitus as major contributors to the mortality in stroke patients with hyponatremia. [21][22][23][24][25][26] More studies are needed however to quantify the effects of hyponatremia on mortality in acute stroke patients, and to find the mortality benefit that we can get by correcting this factor. Similar studies from other centers in the country are also needed see the overall effect of this in our population from different parts of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Another scholar compared the correlation between hs-CRP levels and infarcted volume and found a positive relationship between the 2. The majority of clinical scholars use hs-CRP as an indicator for assessing stroke progress, prognosis, and recurrence [ 22 24 ]. A number of scholars have studied guinea pig brain specimens and blood-brain barrier in vitro cell culture models, which show that CRP induces blood-brain barrier damage, resulting in cerebral edema through a signal transduction pathway [ 25 ].…”
Section: Discussionmentioning
confidence: 99%